(untitled) (American Journal of Business Management, Economics and Banking, 2025)
When analyzing the labor market, it is important to quantify the relationship between the employed population and general indicators that reflect the development of the economy. To do this, the number of people employed in the economy and the factors affecting this indicator, as well as forecast values, were determined. In this regard, it is important to create multifactorial econometric models based on the study of the labor market of our country, taking into account the factors affecting the employment rate.